How Mothers of Children With Autism Spectrum Disorder Think About Their Quality of Life? - Zefanya, Ersa; Purba, Fredrick Dermawan (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Raising a child with autism spectrum disorder (ASD) can be challenging for mothers in many ways, their quality of life: social, physical, psychological, etc. This research explored how mothers with ASD perceive their quality of life and what influences those perceptions. This study employed qualitative research design. A total of 3 mothers were participated, using convenience sampling method in Bandung, West Java. This study using a semi-structured interview with a prepared guideline by the researchers, based on strong framework and theory. A method called content analysis was used to systematically understand the challenges they faced, the coping mechanisms they developed, and finally, the factors they believed would improve their quality of life. The data were analyzed using the content analysis approach. The participants reported a variety of difficulties and their way of coping with the problems, following factors that could help them to raise their quality of life. Results reported into 5 themes, following with 13 sub-themes. The main themes included “challenges”, “fears about the future”, “changes in social interactions”, “happiness & gratitude” and “factors to improve QOL”.Hidup berdampingan dengan anak autism spectrum disorder (ASD) dapat memberikan beberapa dampak negatif pada orang tua termasuk kualitas hidup mereka yang terdiri atas aspek sosial, fisik, psikologis, dll. Penelitian ini bertujuan untuk mengidentifikasi persepi orang tua terkait kualitas hidup yang dimiliki serta hal yang melatarbelakanginya. Penelitian ini menggunakan desain penelitian kualitatif dan teknik convenience sampling. Sebanyak 3 orang tua dari Bandung, Jawa Barat berberpartisipasi dalam penelitian ini. Guna mengumpulkan data, penelitian ini menggunakan semi-structured interview dengan panduan yang telah disusun berdasarkan teori. Selanjutnya, data di analisis menggunakan pendekatan content analysis. Hasilnya diperoleh bahwa Ibumerasakan beberapa kesulitan dan upaya menghadapinya diikuti dengan beberapa faktor yang dapat membantu Ibu meningkatkan kualitas hidupnya. Hasil dari penelitian ini dikelompokkan kedalam 5 tema utama, diikuti dengan 13 sub-tema. Tema utama terdiri atas “tantangan”, “ketakutan tentang masa depan”, “perubahan dalam interaksi sosial”, “kebahagiaan & rasa syukur” dan “faktor untuk meningkatkan QOL”.